A case of Polycythemia: diagnostic dilemma - Meena N. Jadhav; Priya Patil; Rashmi K. Patil; Shreekant K. Kittur; Milind M. Kesarkhane (Tropical Journal of Pathology and Microbiology, 2019)
Approach to a case of polycythemia is initially to distinguish relative from absolute polycythemia; then to distinguish Polycythemia Vera (PV) from secondary polycythemia. Finally, the etiology of secondary polycythemia has to be ascertained. A certain number of patients cannot be easily classified as having either PV or secondary polycythemia due to diagnostic difficulties. We present a case of 52-yearmale, chronic smoker, hypertensive and an asthamatic for whom a complete work up was attempted to rule out PV. There was a diagnostic difficulty as to consider this patient a case of secondary polycythemia or Gaisbock’s syndrome. We were unable to measure the red cell mass in this patient (which will be normal in Gaisbock’s syndrome and increased in secondary polycythemia). Patient underwent phlebotomy and was asymptomatic at discharge.